The correspondence of John Wallis Vol. 2, 1660-September 1668 - Wallis, John, 1616-1703.; Beeley, Philip; Scriba, Christoph J. (Oxford : Oxford University Press, 2004)
This is the second in a six volume compendium on the correspondences of John Wallis (1616-1703). Wallis was Savilian Professor of Geometry at Oxford from 1649 until his death, and was a founding member of the Royal Society and a central figure in the scientific and intellectual history of England.
Correspondence in English or Latin; introduction and notes in English.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Wallis, John, -- 1616-1703 -- Correspondence; Mathematicians -- Great Britain -- Correspondence